Analysis of public health risks from consumption of informally marketed milk in sub-Saharan African countries - Omore, Amos O.; McDermott, John J.; Staal, Steven J.; Arimi, S.M.; Kang'ethe, Erastus K.; Ouma, Emily A. (International Society for Veterinary Epidemiology and Economics, 2000)
Despite policies to discourage them, informal milk markets account for over 80% of milk sales in most sub-Saharan African (SSA) countries. Informal milk market agents include farmer dairy co-operatives, small traders using bicycles and public or private transport and small retail outlets, such as dairy kiosks, and shops. Studies conducted by the International Livestock Research Institute (ILRI) and national collaborators (e.g., in Kenya1) show that convenient delivery and lower prices (reflecting tower handling and processing costs) are the principal benefits for consumers. Current milk handling and safety regulations in most SSA countries are derived from models in industrialised countries. These may not be appropriate for local market conditions where such regulations may unnecessarily inhibit efficient milk marketing. An important step in developing targeted policies more supportive of market participation of the majority is to collect quantitative and qualitative information about milk-borne health risks under different production and marketing situations. This paper gives an over-view of on-going activities in central Kenya aimed at assessing public health risks from informally marketed milk and presents preliminary results of milk quality and handling practices of informal milk market agents and consumers.